Evaluation of University Students’ Cyber Security Awareness and Cyberbullying andCyber Victimization Levels in the COVID-19 Pandemic - Şener, Harun; Arikan, İnci and Gülekçi, Yakup (The Bulletin of Legal Medicine, 2022)
Objective: It is important for young people to recognize the concept of cyberbullying and gain coping skills so that they can fight against cyberbullying/victimization. The aim of this study is to determine the cyberbullying and cyber victimization levels and cyber security awareness of university students during the COVID-19 pandemic. Methods: The questionnaire forms prepared online were answered by 823 students. Survey form includes; the personal data form containing sociodemographic data, questions to measure the level of possession and usage features of information communication tools about cyber security awareness, and Cyberbullying Scale (CBS) and Cyber Victimization Scale (CVS). Results: 3.2% (n:26) of the students reported that they were cyberbullying and 35.1% (n:289) of the students reported that they were cyber-victimized. The median values of CBS and CVS scores were detected as; 1.5 (min:0-max:14) and 9 (min:0-max:30), respectively. The CVS score was found to be higher in those over the age of 22, in female students, in those who use the Internet for more than 5 hours a day besides online classes, and in students who increased the amount of cigarette/alcohol use in the last year (p<0.05). No statistically significant correlation was found between the CBS score and some characteristics of the students (p>0.05). Conclusion: The identification of risk groups exposed to cyber victimization is important in terms of developing future intervention programs and taking measures at the regional level.